Consolidation of functionalized graphene at ambient temperature via mechano-chemistry. (August 2018) - Kabbani, Mohamad A.; Kochat, Vidya; Bhowmick, Sanjit; Soto, Matias; Som, Anirban; Krishnadas, K.R.; Woellner, Cristiano F.; Jaques, Ygor M.; Barrera, Enrique V.; Asif, Syed; Vajtai, Robert; Pradeep, Thalappil; et al.
Abstract: Graphitic solids are typically produced via high temperature and energy consuming processing (e.g. sintering) of carbon particles. Here, we demonstrate the mechano-chemical assembly of functionalized graphene layers into 3D graphitic solids via room temperature and low energy consuming processing. The chemical functional groups on graphene layers are interconnected at room temperature under pressure leading to porous three-dimensional structures with tunable mechanical and electrical properties. The formation of mechano-chemistry induced atomic scale junctions and their impact on mechanical properties of graphene assembled carbon materials are demonstrated through nano-indentation experiments and confirmed using DFT and molecular dynamics simulations. The results show room temperature consolidation routes of graphene layers into bulk carbon solids. Graphical abstract: Image 1